Pakistan’s Nuclear Program: Transformation from Credible Minimum Deterrence to Full Spectrum Deterrence - Siddiqi, Hassam; Shahid, Hina (Journal of Peace, Development and Communication, 2020)
This research paper is based on the concepts related to Pakistan’s nuclear program and nuclear posture adopted by it in the start. This starts from the concept of Credible Minimum Deterrence, which was adopted by Pakistan after becoming nuclear power. At that time Pakistan’s economic condition and strategic interests only allowed Pakistan to go for war denying deterrence to balance the threat caused by India’s conventional superiority over Pakistan. It required a minimum number of weapons to deter. Later on with the technological developments in Indian nuclear program, changes on regional level, Indian civil military deals with USA and introduction of Cold Start Doctrine compelled Pakistan to go for technological improvements in its nuclear missile program and change in its nuclear posture. Furthermore, it is explained in the paper that Pakistan has now decided to go for Full Spectrum Deterrence to respond Indian Cold Start Doctrine. Full Spectrum Deterrence is to make sure that there are no gaps left in Pakistan’s deterrence capability. The objective of this paper is to understand the concepts related to Pakistan’s evolving nuclear posture and the challenges faced by FSD in present.